Commodities and monetary policy: Implications for inflation and price level targeting - Don Coletti; René Lalonde; Paul Masson; Dirk Muir; Stephen Snudden (Bank of Canada, 2012)
We examine the relative ability of simple inflation targeting (IT) and price level targeting (PLT) monetary policy rules to minimize both inflation variability and business cycle fluctuations in Canada for shocks that have important consequences for global commodity prices. We find that commodities can play a key role in affecting the relative merits of the alternative monetary policy frameworks. In particular, large real adjustment costs in energy supply and demand induce highly persistent cost-push pressures in the economy leading to a significant deterioration in the inflation - output gap trade-off available to central banks, particularly to those pursuing price level targeting.
Keywords: E17; E31; E37; E52; F41; Q43; 330; Economic models; Inflation and prices; International topics; Monetary policy framework